Design of Branch Definition Algorithm for Top-k Inverse Queries for Image Processing - Haixia Zhang; Qingxiu Peng (Applied Bionics and Biomechanics)
Images are the main way for human beings to obtain and exchange information, and they play a crucial role in the process of human understanding and exploration of the world. Top-k inverse queries are widely used in real life. Currently, the most efficient algorithm for computing top-k inverse sets is the inverse top-k algorithm. Our algorithm is significantly limited when dealing with top-k inverse queries. To address these limitations, an intuitive branch-and-bound algorithm is proposed to efficiently handle top-k inverse queries, and novel optimization methods are discussed to mention its high performance. Experimental evaluation shows that the algorithm is far more efficient than the inverse top-k algorithm.